KONSTRUKSI IDEAL PEMANFAATAN HUKUM KESEHATAN DALAM PELAYANAN KESEHATAN DI RUMAH SAKIT BERBASIS NILAI KEADILAN - Budiman, Arif (LPPM Universitas Bina Bangsa, 2024)
Increasing public knowledge about the health of the increasing criticism and demands on health services provided by health providers, application and utilization of health law at this time is not maximized, this proved not their field or special sections health care law itself both in the hospital and health services other. The negative impact is still an element of discrimination among health professions, the incidence rate is still high malpractice as was the case recently occurred, the patient died in Jakarta Chiropractic Clinic and the rampant cases of trade in human organs. With the increasing incidence of malpractice so prevention is indispensable to the health law priority in health services in hospitals based on values of justice